Applying threshold concepts to finance education. Issue 5 (13th June 2016) - Hoadley, Susan; Wood, Leigh N; Tickle, Leonie; Kyng, Tim
Abstract : Purpose: – The purpose of this paper is to investigate and identify threshold concepts that are the essential conceptual content of finance programmes. Design/methodology/approach: – Conducted in three stages with finance academics and students, the study uses threshold concepts as both a theoretical framework and a research methodology. Findings: – The study identifies ten threshold concepts in finance that are clearly endorsed by finance academics. However, the extent to which students are explicitly aware of the threshold concepts in finance is limited. Research limitations/implications: – As well as informing further research into the design and delivery of finance programmes, the findings of the study inform the use of threshold concepts as a theoretical framework and a research methodology. The study does not explore the bounded, discursive, reconstitutive and liminal aspects of threshold concepts. Implications include the lack of recognition of more modern concepts in finance, and the need for input from industry and related disciplines. Practical implications: – The threshold concepts in finance provide the starting point for finance educators in the design and delivery of finance programmes. In particular, the threshold concepts in finance need to be made more explicit to students. Social implications: – Using the threshold concepts in finance as well as the other findings of this study to inform to finance curriculum design and delivery is likely to achieve better quality educational outcomes for finance students as well as better prepare them for professional finance roles. Originality/value: – The finance curriculum is under researched and for the first time this study identifies the threshold concepts in finance to inform the design of finance programmes.